FACILE SYNTHESIS AND SIZE DISTRIBUTION ANALYSIS OF SILVER NANOPARTICLES OF FUNGUS Penicillium crustosum, ISOLATED FROM Taxus baccata Linn. (Applied Biological Research, 2023)
The present study was aimed at the synthesis and size distribution analysis of  silver nanoparticles (AgNPs), from a fungal endophyte Penicillium  crustosum. The fungus was isolated from the needles of Taxus baccata Linn. and identified as Penicillium crustosum by molecular characterization. The  fungal extract of P. crustosum was subjected to the synthesis of AgNPs. UV vis-spectroscopy confirmed the formation of AgNPs by forming the specific  peaks at 390-450 nm. The lyophilized AgNPs were subjected to size  distribution analysis using tools like X-ray diffraction, energy dispersive  spectroscopy (EDS), field emission scanning electron microscopy (FEG SEM), and high-resolution transmission electron microscopy (HRTEM). The  average crystalline size of AgNPs was calculated by Debye-Scherrer’s  formula which showed AgNPs of 36.93 nm. These findings substantiated the  results of FEG-SEM and HRTEM, where the average size was below 50 nm.  Dynamic light scattering results showed Z-average of AgNPs as 352.0 rnm  with 0.982 PdI. Zeta potential was -19.1 mV which showed the capacity of  formed AgNPs to decline agglomeration. EDS analysis proved that the  requisite phase of silver is present in the sample. The present study displayed  the potential of P. crustosum as reducing agent which converted silver ions  into AgNPs in eco-friendly and cost-effective manner.
Keywords: Energy dispersive spectroscopy; HRTEM; Penicillium crustosum; silver nanoparticles; Taxus baccata